Civil society demands in the participation areas of the Master Plan and Urban Mobility Plan of Ponta Grossa - Pr - Pacheco, Juliana Thaisa Rodrigues; Yuri Kawanish , Juliana; Rolim de Moura , Reidy; Scheffer, Sandra Maria (Temporalidades, 2020)
New guidelines for Urban Planning are established from the Federal Constitution of 1988 and the Statute of Cities (Law 10.257 / 01), among these guidelines the popular participation as a society representation stands out, which enabled participation in moments decision-making processes for public actions and policies. With this focus in mind, this article aims to identify the actors involved in popular participation and what points were discussed by these actors in the review of the Master Plan and in preparation of the Urban Mobility Plan in Ponta Grossa - Pr. The data collection was organized based on seven community workshops and four public hearings from June 2018 to March 2019. The methodology used was exploratory and descriptive research, quantitative data were collected from attendance lists, photographic records and direct participant observation. The results reveal the importance of participation in the process of building the Master Plan and the Mobility Plan.